Discoloration of sunfix yellow S4GL dye using H 2 O 2 /UV advanced oxidation process - Aldeir Pinedo, Fernando Anaya (2017)
A study of the kinetics of discoloration of a 20 ppm solution of Sunfix Yellow S4GL (RAS) reactive dye has been carried out using the H2O2/UV advanced oxidation process (AOP). To optimize the process, the effects on the discoloration of the initial concentration of hydrogen peroxide, the initial pH of the solution, the dye concentration and the intensity of the UV‐ C radiation were evaluated. The optimum values were the following: initial concentration of H2O2 a 3.8 x 10‐2 mol/L, pH3; initial dye concentration: 20 mg/L; UV radiation: 3 bulbs with 15 W of UV‐C power each. The discoloration reaction followed a pseudo first order kinetic model. Under optimum conditions, a one hour treatment yielded 100% discoloration.